Secondary syphilis psoriasiform in HIV-infected patients: A case series - Fitriani, Katia; Alessandro Alfieri; Nurwestu Rusetiyanti; Devi Artami Susetiati; Niken Trisnowati; Satiti Retno Pudjiati (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Psoriasiform secondary syphilis is an uncommon and diagnostically challenging variant of secondary syphilis that can closely mimic psoriasis vulgaris, particularly in people with HIV. This case series adds to the limited literature from resource-limited settings by illustrating how psoriasiform secondary syphilis may be misinterpreted as psoriasis both clinically and histopathologically, and how repeated clinicopathologic correlation is essential to avoid inappropriate immunosuppression. We reported three HIV-infected male patients who presented with generalized psoriasiform erythematous scaly plaques, some with palmoplantar involvement, initially diagnosed as psoriasis. One patient had been treated with methotrexate for severalmonths without clinical improvement. Serologic testing in all cases demonstrated active syphilis with reactive nontreponemal and treponemal tests, including a very high venereal disease research laboratory (VDRL) titer in one patient, and all were confirmed HIV-positive. Initial histopathologic examinations variably suggestedsecondary syphilis or psoriasis; in two patients, repeat biopsy or deeper sectioning was required to reveal plasma cell–rich perivascular infiltrates and vascular changes consistent with secondary syphilis, while one case was ultimately considered to represent coexistence of psoriasis and syphilis. All patients received intramuscularbenzathine penicillin G according to syphilis stage, with additional topical or systemic antiinflammatory therapy when indicated, and showed clinical improvement. In conclusion, psoriasiform secondary syphilis should be routinely considered in the differential diagnosis of psoriasiform eruptions in individuals with sexuallytransmitted infection risk or known HIV infection, and that discrepant clinical, serologic, and histopathologic findings warrant repeat biopsy, deeper sectioning, and multidisciplinary review.